A multicenter cohort study on the association of the one‐abutment one‐time concept with marginal bone loss around bone level implants. Issue 2 (20th December 2020) - Lambrechts, Tijs; Doornewaard, Ron; De Bruyckere, Thomas; Matthijs, Liesbet; Deschepper, Ellen; Cosyn, Jan
Abstract: Objectives: To investigate the association of the one‐abutment one‐time concept with marginal bone loss (MBL) around bone‐level implants in relation to other factors. Materials and methods: Records from patients treated by four experienced implant surgeons between January 2016 and July 2019 were scrutinized. Subjects treated with two bone‐level implant types with varying machined collar (subgroups: 0.5 and 0.8 mm) were considered, receiving a healing abutment (HA cohort) or a permanent abutment at the time of surgery (OT cohort). The primary outcome was MBL registered at 3 months and the longest follow‐up. A clustered two‐part regression model for semicontinuous data was used. Results: Data pertaining to 160 patients (92 females, mean age 54) and 344 implants (125 in HA cohort, 219 in OT cohort) were available for evaluation. Mean MBL amounted to 0.52 mm ( SD 0.68) after a mean follow‐up of 20 ( SD 9.2) months, with 33.8% of the implants showing complete bone preservation and 5.0% demonstrating >2mm MBL. OT was not related to the presence of MBL using MBL as dependent binary variable (0: no MBL; 1: MBL irrespective of its magnitude). However, OT significantly reduced the magnitude of MBL with 0.300mm when compared to HA ( p = .023) in the cases where MBL was detected. Subgroup ( p = .212 ), smoking ( p = .789 ), history of periodontitis ( p = .839 ), type of edentulism ( p = .054 ), implant surgeon ( p = .079 ), patient compliance ( p = .617 ), and follow‐up ( p = .443 ) failed to show a significant association with MBL in the regression model. Ninety‐eight % of the implants survived. Conclusion: Within the limitations of a cohort study, the one‐abutment one‐time concept was associated with a decrease in MBL at implant sites with bone loss. Therefore, the placement of a permanent abutment at the time of surgery seems relevant to limit marginal bone‐level alterations.